Taboo words in hate speech through Social Media - Husda, Azizah; Saragih, Elza Leyli Lisnora; Mulyadi, Mulyadi (Technium Social Sciences Journal, 2021)
This research is on taboo words used in hate speech through social media to find out the classification of taboo words and to describe the social functions of taboo words in hate speech. The method applies descriptive qualitative by describing taboo words. The data were obtained through documents from social media about recently updated hate speech. The synthesis of some previous theories and relevant studies support the research. The approaches used is socio-semantics as the combination of both sociolinguistics and semantics, because it studies the meanings and perspectives of using taboo words among society in hate speech. The findings showed that there are taboo words classified into epithets, profanity, vulgarity, obscenity, cursing and supernatural beings. The functions of using taboo words were also found to draw people’s attention, to show contempt, to provoke, and to mock authority. This research finally provides some contributions and references for any further research related to the use of taboo words within any language and also as communication guidance especially for speakers to avoid using taboo words which lead to hate speech.